EFFECTS OF CLASSROOM PEER COLLABORATION AMONG SECONDARY SCHOOLS STUDENTS’ ACHIEVEMENT IN MATHEMATICS: IMPLICATION FOR COUNSELLING - Amede Lucky (Indonesian Journal of Learning and Instruction)
This study examined the effects of classroom peer collaboration among secondary schools students’ achievement in Mathematics. Three hypotheses questions guided the study. The design used was the pretest-posttest quasi-experimental research design since data were collected before and after treatment. The population of this study consisted of all the secondary schools students in Ukwuani, Delta state, Nigeria. The sample used for this study was 100 secondary schools students from two (2) secondary schools in Ukwuani Local Government area in of Delta state. Two intact classes of Senior secondary 2 were used for the study.The research was conducted in the two selected secondary school for a period of 10weeks. The researcher administered the questionnaire (PCI) to the subjects in two instances, a week prior to the treatment (pretest) and a week after the treatment (posttest). Treatment was based on the elaborate treatment package that specified contents and objectives. The pretest scores were used for the baseline comparison for the posttest statistical analysis. Within the period of the experiment, the control group 2 was taught without instructional materials. Subjects in the experimental group one were told to keep the benefits gained from the lessons to themselves at least during the period of the study to minimize confounding effects on the study. Data obtained were tested with Analysis of Covariance (ANCOVA), the t test statistic and the one way ANOVA because of their appropriateness to the hypotheses. The outcome of the study revealed that there is a significant effect of classroom peer collaboration on students’ achievement in Mathematics in secondary schools in Ukwuani, Delta state, Nigeria. There is a significant difference between male and female and age stratifications on classroom peer collaboration on students achievement in Mathematics in secondary schools in Ukwuani, Delta state, Nigeria. From the research findings, it can be concluded that students learn better through peer groups rather than general classroom teaching. They are free to express themselves and to reveal their weak areas to their peers rather than to teachers. Mathematics is a broad subject, so peer learning should be encouraged in all schools both public and private schools to enhance students’ performance in the subject.  Key Words: Peer collaboration, academic achievement, Mathematics, counselling